An Evaluation of World Bank Assistance to China for Poverty Reduction in the 1990s - Khan, A.R. (World Bank, Washington, DC, 2014)
This paper attempts an evaluation of World Bank s assistance to China for poverty reduction during the 1990s. It begins with a summary of China's performance in poverty reduction during the decade as a backdrop to the subject in section two. Section three, presents an analysis of the causes why China's performance in poverty reduction was not faster during this decade of extraordinarily rapid growth. Section four briefly considers the evolution of China's strategy for poverty reduction. Section five, the central section of the paper, discusses the role of the Bank's main instruments - economic and sector work; and lending operations in helping China alleviate poverty. Section six considers future priorities for Bank strategy in China to help accelerate the reduction of remaining poverty in the country.